2018
DOI: 10.1371/journal.pmed.1002534
|View full text |Cite
|
Sign up to set email alerts
|

HIV treatment eligibility expansion and timely antiretroviral treatment initiation following enrollment in HIV care: A metaregression analysis of programmatic data from 22 countries

Abstract: BackgroundThe effect of antiretroviral treatment (ART) eligibility expansions on patient outcomes, including rates of timely ART initiation among those enrolling in care, has not been assessed on a large scale. In addition, it is not known whether ART eligibility expansions may lead to “crowding out” of sicker patients.Methods and findingsWe examined changes in timely ART initiation (within 6 months) at the original site of HIV care enrollment after ART eligibility expansions among 284,740 adult ART-naïve pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 40 publications
(44 reference statements)
7
36
0
Order By: Relevance
“…Similar results were observed even when excluding patients who were not eligible for ART prior to Treat All implementation, indicating that the change was not solely due to the new guideline and its implementation at the sites, but rather in improved programme capacity to rapidly initiate ART. These data are consistent with successful implementation of earlier ART guidelines in Rwanda leading to rapid increases in median CD4 count at ART initiation, as well as global data showing rapid increases in ART uptake as treatment thresholds increased .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were observed even when excluding patients who were not eligible for ART prior to Treat All implementation, indicating that the change was not solely due to the new guideline and its implementation at the sites, but rather in improved programme capacity to rapidly initiate ART. These data are consistent with successful implementation of earlier ART guidelines in Rwanda leading to rapid increases in median CD4 count at ART initiation, as well as global data showing rapid increases in ART uptake as treatment thresholds increased .…”
Section: Discussionsupporting
confidence: 83%
“…Among patients enrolling in care after Treat All implementation, we did not find an association between baseline CD4 count and 30‐day ART initiation. Prior studies, including the Treatment as Prevention trial, have demonstrated that treatment expansion does not result in delayed ART initiation among sicker patients . To our knowledge, our study is the first to confirm these findings within a routine implementation of a Treat All paradigm.…”
Section: Discussionsupporting
confidence: 75%
“…In addition, in some settings, routine HIV viral load monitoring is infrequent, and pre‐ART CD4 count monitoring is declining in frequency with Treat All implementation , which limits opportunities to evaluate individual and public health impacts of HIV programming. Four key metrics for assessing the timeliness of continuum milestones include: (1) median CD4 count at diagnosis , care enrollment , and ART initiation ; (2) time between diagnosis, enrollment ; (3) time between enrollment and ART initiation ; and (4) time to first HIV viral suppression and sustained HIV viral suppression. Research approaches : Metrics for this research priority could be generated from routinely collected, patient‐level, programmatic data. Where CD4 count and viral load data are not readily available for a large enough proportion of clinics and patients, it may be possible to produce estimates from a systematic sample of sites.…”
Section: Resultsmentioning
confidence: 99%
“…at higher CD4 counts) and linkage to care are needed. Although more real‐world data on timely ART uptake under Treat All implementation are needed, early evidence on ‘Treat All’ in SSA and evidence from previous HIV treatment guideline expansions suggest that if people are eligible for treatment when they link to care, they will start ART rapidly with early retention in care and viral suppression following ART initiation .…”
Section: Discussionmentioning
confidence: 99%
“…Temporal trends in time to cART initiation in Latin America in asymptomatic patients with high CD4 cell counts have not been evaluated previously, though several studies have explored time to cART initiation overall, also showing trends towards earlier cART initiation over time . Of note, most studies done looking at time to cART initiation look at CD4 count at the time of cART initiation, rather than median time (in days or years).…”
Section: Discussionmentioning
confidence: 99%